Differential effects of six structurally related benzodiazepines on some ethological measures of timidity, aggression and locomotion in mice - Krsiak, M; Sulcova, A (Psychopharmacology, 1990)
The effects were compared of three 2' chlorophenyl-benzodiazepines (triazolam, clonazepam and lorazepam) and three corresponding 2' deschloro-phenyl-derivatives (alprazolam, nitrazepam and oxazepam, respectively) on the incidence of six ethological elements in both timid and aggressive singly-housed male mice, treated with drugs in paired interactions with untreated non-aggressive males. Alprazolam and oxazepam reduced defensive upright postures and escapes at doses which did not reduce rearing and actually increased walking, while their chlorinated counterparts (triazolam and lorazepam, respectively) decreased incidence of defenses and escapes mostly at doses decreasing locomotor acts involving a similar movement (rears and walks, respectively). Alprazolam and oxazepam also reduced attacks at doses not reducing rears, in contrast to triazolam and lorazepam which reduced attacks only at doses suppressing rearing. Nitrazepam stimulated sniffing partners much more than its chlorinated counterpart clonazepam. The 2' deschloro-phenyl-benzodiazepines were more potent in reducing defensive-escape activities than attacks or locomotion. Yet, none of the benzodiazepines tested produced a complete inhibition of timid defensive-escape behavior at non-sedative doses. The present study suggests that 2' deschloro-phenyl-benzodiazepines are less "sedative" with respect to their "anxiolytic" activity.
Keywords: pohybová aktivita; chování zvířat; alprazolam; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; plachost; lorazepam; Nitrazepam; oxazepam; Alprazolam; Shyness; zvířata; myši; anxiolytika; Clonazepam; Mice; nitrazepam; Oxazepam; Anti-Anxiety Agents; Triazolam; Male; Lorazepam; agrese; klonazepam; Motor Activity; Animals; triazolam; mužské pohlaví; Aggression; Behavior, Animal